Active galactic nuclei: global perspective and time-domain implications - Kazanas, Demosthenes (Frontiers in Astronomy and Space Sciences, 2024)
We present a view of the global structure of AGN following the detection of blue-shifted Warm Absorber (WA) and Ultra Fast Outflows (UFO) absorption features in their X-ray spectra.Straightforward interpretation of these features suggests the presence of MHD winds off the underlying accretion disks that span a wide range in radius, from a few to ∼ 10 6 Schwarzschild radii. UFOs are associated with the wind segments closest to the black hole, with decreasing ionization absorber species associated with wind segments at increasingly larger distances; eventually, the wind segments at the largest distances are sufficiently cool and dusty to be associated with the so-called AGN tori, as suggested in the past. Furthermore, spectroscopic X-ray observations of sufficient resolution allow estimates of the winds' mass flux, to show that it increases with radius. As a consequence, the mass flux of the underlying accretion disk must decrease toward the accreting black hole, reaching eventually a value smaller than that needed to convert the flow into an X-ray hot, Advection Dominated Accretion Flow; we suggest that this hot segment of the accretion flow is responsible for the observed AGN (and Galactic X-ray binaries) X-rays, in place of the ad hoc so far assumed corona. We indicate that the properties of this component, reflected in its relative luminosity to its viscous disk O-UV component depends on the source luminosity in broad agreement with observation.